Bulk Viscous Bianchi Type VI0 Cosmological Model in the Self-creation Theory of Gravitation and in the General Theory of Relativity - E. A. Hegazy (Iranian Journal of Astronomy and Astrophysics)
In the second self-creation theory of gravitation and in the general theory of relativity, Bianchi type VI0 cosmological model in the presence of viscous fluid is studied. An exact solution of the field equations is given by considering the cosmological model yields a constant decelerations parameter q=constant and the coefficients of the metric are taken as A(t)=[c1t+c2]3L/(q+1)(L+1), B(t)=[c1t+c2]3/2(q+1)(L+1),C(t)=[c1 t+ c2]3/2(q+1)(L+1),where c1,c2 and L are constants . Effect of the viscosity on the entropy of the universe is given by a composition of the second law of thermodynamics with the the energy momentum tensor Tji with bulk viscous term in a conservative manner. We obtained a formula for calculation the entropy of the universe in term of the viscosity and used it to study and compare the Entropy, Enthalpy, Gibbs energy and Helmholtz energy of the universe in the presence of viscosity term in the self-creation theory of gravitation and in the general theory of relativity. The physical and geometrical properties of the obtained models are discussed.